Iowa CBC reporting form, Yellow River Forest, January 4, 1986 - Koenig, Darwinet al (1986)
Checklist dated January 4, 1986 compiled by Darwin Koenig. A list of birds sighted by Koenig and eight others at Yellow River Forest. A total of 37 species and 1,721 individual birds were sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Winter 1985-1986. Epson - sheet feed